CD44 Expression in Papillary Thyroid Carcinoma and its Correlation with Prognostic Factors - Fatemeh Baghertash; Mohammadreza Jalali Nadoushan (Journal of Mazandaran University of Medical Sciences, 2023)
Background and purpose: Identifying the prognostic factors of malignancies is of particular importance in therapeutic decisions and identification of high-risk patients. Since the papillary thyroid carcinoma (PTC) is the most common thyroid malignancy, we aimed to investigate the expression and prognostic role of CD44 in patients with PTC. Materials and methods: This cross-sectional study was performed in patients with PTC who underwent thyroidectomy in Tehran Mostafa Khomeini Hospital, 2015-2019. Demographic information, and macroscopic and microscopic characteristics of the tumor were extracted from pathology reports. CD44 expression was classified from negative to extremely positive. We assessed the correlation between CD44 expression and patients' demographic characteristics and clinicopathological characteristics of the tumor. Results: Eighty PTC patients (58 females and 22 males) with a mean age of 40.85±4.59 years were studied. The frequency of lymph node and capsule invasion were 27.5% and 48.8%, respectively. The mean tumor size was 3.55±2.27 cm. All patients had more than 5% CD44 expression. Strongly positive and extremely positive cases of CD44 expression accounted for 43.8% and 21.3% of the cases, respectively. There was no significant difference in CD44 expression according to sex, age, and tumor size (P> 0.05). But, CD44 expression was found to be significantly associated with lymph node invasion (OR= 7.55) and especially capsule invasion (OR= 24.52). Conclusion: Considering the relationship between CD44 expression and capsule and lymph node invasion in PTC, this biomarker can be used as a prognostic factor of more invasive disease in patients with PTC.